Sexual dimorphism in the DNA methylation pattern after immune stimulation in the zebrafish (Danio rerio) gonads - Salazar, M.; Caballero-Huertas, M.; van Gelderen, T. A.; Krabbe, M. N.; Gut, M.; Heath, S.; Esteve, A.; Ribas, L. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionIn fish, epigenetic modifications are fundamental for regulating development, growth and adaptation to environmental factors. Emerging evidence further suggests that epigenetic mechanisms may modulate how fish gonads respond to infectious agents. Gonadal factors—including reproductive hormones and cytokines—are known to influence immune-cell activities, regulate the production of immune molecules, affect the overall immune response, and participate in gonadal sex differentiation. Although interactions between the reproductive and immune systems are well established, the epigenetic mechanisms underlying this interaction remain insufficiently elucidated, both in fish and in mammals. This study investigates how immune stimulation affects sex differentiation and methylation patterns of innate-immune genes in zebrafish gonads.MethodsTo study the epigenetic events involved in the immune–reproduction interaction, zebrafish (Danio rerio) were immune-stimulated with lipopolysaccharide (LPS) using two experimental approaches. (1) To assess the effect of immune stimulation on sex ratio, larvae were bathed in LPS during gonadal development (17–30 days post-fertilization, dpf). (2) To examine DNA methylation patterns in response to immune stimulation in adulthood, sexually mature fish received intraperitoneal LPS injections. Methylation analyses focused on two key innate immune genes, caspase 9 (Casp9) and interleukin 1β (Il1β). DNA methylation was quantified using a candidate-gene approach at single-nucleotide resolution through sequencing of bisulfite-converted DNA.ResultsImmune stimulation during gonadal development did not produce a statistically significant difference in sex ratio, although a clear trend toward feminization was observed in LPS-treated fish. In adults, Casp9 exhibited significant DNA-methylation differences driven by the interaction between treatment and sex. Specifically, eight CpG sites were significantly altered in treated females, while three CpG sites were significantly altered in treated males. In contrast, Il1β showed a sexually dimorphic methylation pattern, but these differences were not attributable to immune stimulation.DiscussionThe results support the presence of an epigenetic interplay between sex and immune response in the fish gonads. Sex-dependent methylation changes in Casp9 following LPS exposure, together with the inherent sexual dimorphism observed in Il1β, indicate that immune stimulation and sex jointly shape epigenetic landscapes of innate immune genes in reproductive tissues. Although the feminization effect was not statistically significant, the observed trend suggests that immune activation during the critical gonadal differentiation window may influence sex outcomes. Overall, these findings contribute to a deeper understanding of the epigenetic mechanisms underlying sexually dimorphic immune responses in reproductive tissues and highlight important avenues for future research.